Awareness and practice towards dengue fever in Kannamangala village, Bangalore, Karnataka, India - C., Pradeep; K. S., Achuth; S., Manjula (International Journal Of Community Medicine And Public Health, 2016)
Background: Dengue is a mosquito-borne viral infection of humans. The agent causing dengue is a single-stranded RNA virus of Flaviviridae family. In recent years dengue hemorrhagic fever has become a global public health problem. Urbanization and poor management of garbage in the city limits has resulted in increase in the breeding site for Aedes aegypti which is a vector for dengue fever. The aim and objective was to assess the knowledge, awareness and practices towards dengue fever in Kannamangala village. Methods: This community based cross sectional study was conducted in Kannamangala village from July 2014-December 2014. Totally 738 participants were enrolled in the study. The aim was to assess the knowledge and awareness, preventive measures and most prevalent source of information regarding dengue by using semi-structural questionnaire. Results: Knowledge and practice regarding dengue fever is not satisfactory, 60% of the respondents said dengue is a serious illness and 68.8% said it is transmitted through mosquito bite and only 8% knew the name of the vector. Only 15.3% of the participants changed water in artificial container every week, 49.2% of the respondents got the information from Radio/TV followed by Newspaper/magazine. Only 15.4% of the respondents received information by Health personnel. Conclusions: Lack of awareness and improper practice towards dengue is explicit in this study. Emphasis should be more on creating awareness among people. Educational intervention has to be more effective in controlling dengue fever.